Lessons Learned From a Colocation Model Using Psychiatrists in Urban Primary Care Settings. (July 2013) - Weiss, Meredith; Schwartz, Bruce J.
Objectives: Comorbid psychiatric illness has been identified as a major driver of health care costs. The colocation of psychiatrists in primary care practices has been proposed as a model to improve mental health and medical care as well as a model to reduce health care costs.Methods: Financial models were developed to determine the sustainability of colocation.Results: We found that the population studied had substantial psychiatric and medical burdens, and multiple practice logistical issues were identified.Conclusion: The providers found the experience highly rewarding and colocation was financially sustainable under certain conditions. The colocation model was effective in identifying and treating psychiatric comorbidities.